Dietary vitamin B9 intake linked to drug-resistant epilepsy risk in western Chinese adults: exploring underlying metabolomic mechanisms - Zhang, Ling; Liu, Ling (Frontiers in Nutrition, 2025)
IntroductionApproximately 30% of epilepsy patients develop drug-resistant epilepsy (DRE), underscoring the need for adjunctive therapies. While dietary interventions like the ketogenic diet show promise, evidence for specific micronutrients, particularly regarding differences between DRE and non-drug-resistant epilepsy (NRE), remains scarce. This study investigated B-vitamin intake and plasma metabolomic profiles in NRE versus DRE patients.MethodsWe established a cohort of 330 adults with epilepsy (165 NRE, 165 DRE) from western China. Dietary intake of vitamins B1, B6, B9, and B12 was assessed. Multivariate logistic regression and restricted cubic splines (RCS) analyzed associations between vitamin intake and DRE risk. Stratified analyses evaluated consistency across subgroups. Untargeted metabolomics was performed on a subset of patients to identify differential metabolites and pathways.ResultsIn the fully adjusted model, only dietary vitamin B9 (folate) intake was significantly and inversely associated with DRE risk (OR: 0.78 per 100 μg, 95% CI: 0.64–0.94; p = 0.01). The RCS indicated a linear dose-response relationship (non-linearity p = 0.412). This protective association remained stable across various subgroups without significant interactions. Metabolomic analysis revealed distinct profiles between NRE and DRE, identifying key differential metabolites including decreased linoleic acid and tetrahydrofolyl-glutamate, and increased cortisol. Pathway analysis implicated alterations in linoleic acid metabolism, cortisol synthesis and secretion, and folate metabolism.ConclusionThis study identifies lower dietary vitamin B9 intake as an independent risk factor for DRE in a Chinese adult cohort, with each 100 μg increase conferring a 22% reduction in risk. The metabolomic findings provide potential mechanistic insights, linking folate intake to dysregulated stress hormone, inflammatory, and one-carbon metabolism pathways in DRE. These results highlight the potential of nutritional assessment and intervention in the management of drug-resistant epilepsy.